2022
DOI: 10.3390/ma15144816
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Superhydrophobic Surface on Copper Substrate with Dealloying-Forming and Solution-Immersion Method

Abstract: In this study, a superhydrophobic surface was constructed on a copper substrate through dealloying-forming and solution-immersion methods. The dealloying process for nanostructures on a copper surface involved the electrodeposition of zinc atoms, and the thermal alloying and chemical dealloying of zinc atoms. Then, a dealloyed copper surface was subsequently modified with low-surface-energy copper stearate to produce a superhydrophobic surface. Scanning electron microscopy, X-ray diffractometry, and Fourier tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…This is probably ascribed to the extending coverage of the copper substrate with the flower-like copper stearate morphologies that either cover the original silver leaf morphologies or destroy them during the stacking of the nanosheets of the copper stearate. Similar behavior was observed in [49] where the copper stearate morphologies prevailed over all other formed nanostructures when the immersion time was increased. detachment.…”
Section: Oil-water Separationsupporting
confidence: 76%
See 1 more Smart Citation
“…This is probably ascribed to the extending coverage of the copper substrate with the flower-like copper stearate morphologies that either cover the original silver leaf morphologies or destroy them during the stacking of the nanosheets of the copper stearate. Similar behavior was observed in [49] where the copper stearate morphologies prevailed over all other formed nanostructures when the immersion time was increased. detachment.…”
Section: Oil-water Separationsupporting
confidence: 76%
“…The acidic environment of the ethanolic stearic acid solution oxides the copper and releases Cu 2+ ions which are then captured by the stearic acid and precipitate as copper stearate, as confirmed by FTIR analysis, in the form of nanosheets. Possible occurring reaction is shown in Equation ( 3) [49]:…”
Section: Effect Of Immersion Timementioning
confidence: 99%
“…20 Electrodeposition stands out as a well-established industrial process that can be used in superhydrophobic surface fabrication due to its facility, scalability, and high efficiency. Various metals, including nickel, 21 nickel graphite, 12 zinc, 22,23 and copper 24,25 have been successfully deposited for this purpose. In most cases, a modification step completes the superhydrophobization procedure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jie et al demonstrated a combining dealloying and heating approach to achieve a superhydrophobic surface on brass [ 25 ]. Li et al prepared a superhydrophobic copper substrate through a dealloying and subsequent coating method [ 26 ]. Although the dealloying technique without surface coating has been utilized to acquire the superhydrophobicity on alloy surfaces [ 26 , 27 ], the development of the superhydrophobic membrane only by dealloying for oil/water separation has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%